Family, an agent of early childhood care in preterm children: social outreach flanking - Garrido Sandino, Lupita; Morales Piedra, Yisley; Madriz Bermúdez, Linda (Innovaciones Educativas, 2020)
Since 2016, the Department of Conceptualization of Special Education at Universidad Estatal a Distancia has been developing the outreach project “UNED in action: Promoting new opportunities for children exposed to biological or social risk factors.” The objective is to promote educational actions to train and empower families and caregivers of preterm children in early care (Atención Temprana, AT) with biological and social risk factors between ages 0 - 6 for their comprehensive development. Families of preterm children get orientation, especially considering that 10% of births in Costa Rica are preterm. Theory indicates that AT can revert the effects of this risk factor. Families need to understand what AT is, but they cannot always have access to the recommended practices or are unaware of their importance, fact that is accentuated outside the Greater Metropolitan Area where related services are limited or inexistent. University outreach programs allow for joint guidance and instruction with the families, which empowers them as change agents that overcome the traditional paradigm regarding early childhood stimulation conventionally framed under a clinical model where the specialist was the only one bestowed with knowledge. Via a methodological line of action research, the project offered workshops based on games and family learning. From 2017 to 2019, it was worked with eighty-eight participants in different provinces. The success element that favored family empowerment was basing the project on AT, promoting daily activities as learning experiences, the very philosophy of the research that originated the process.